Biologia molecular da movimentação ortodôntica - Massarelli, Eduardo Ernst (2011)
In the last decade, molecular biology has been a study tool increasingly present in orthodontic research. The orthodontist who aspire excellence in their clinical practice must be aware of new knowledge that emerges revealing the molecular basis of orthodontic tooth movement. The focus of this study is three key molecules that regulate the differentiation and activation of osteoclasts and, ultimately, bone resorption witch is necessary for orthodontic movement. They are the Receptor Activator of Nuclear kappa β (RANK), its ligand (RANKL) and Osteoprotegerin (OPG). The aim of this study was to conduct a literature review of the role of these molecules in orthodontic movement, as well as the tools that the orthodontist has to influence it, nowadays or in the near future, to ensure his patient an orthodontic treatment more effective and safe. Through scientific analysis, it was concluded that, by changing the direction, magnitudes and duration of orthodontic force, the orthodontist can interfere with the expression pattern of RANKL and OPG in periodontal ligament. Nevertheless, the use low level laser therapy to increase orthodontic movement presents itself as a therapy to be used in the near future, as well as the drugs that ensure better containment post-treatment by inhibition of tooth movement.